Induction of IL-12p40 and type 1 immunity by Toxoplasma gondii in the absence of the TLR-MyD88 signaling cascade. - Lindsay M Snyder (Public Library of Science (PLoS), 2021)
Toxoplasma gondii is an orally acquired pathogen that induces strong IFN-γ based immunity conferring protection but that can also be the cause of immunopathology. The response in mice is driven in part by well-characterized MyD88-dependent signaling pathways. Here we focus on induction of less well understood immune responses that do not involve this Toll-like receptor (TLR)/IL-1 family receptor adaptor molecule, in particular as they occur in the intestinal mucosa. Using eYFP-IL-12p40 reporter mice on an MyD88-/- background, we identified dendritic cells, macrophages, and neutrophils as cellular sources of MyD88-independent IL-12 after peroral T. gondii infection. Infection-induced IL-12 was lower in the absence of MyD88, but was still clearly above noninfected levels. Overall, this carried through to the IFN-γ response, which while generally decreased was still remarkably robust in the absence of MyD88. In the latter mice, IL-12 was strictly required to induce type I immunity. Type 1 and type 3 innate lymphoid cells (ILC), CD4+ T cells, and CD8+ T cells each contributed to the IFN-γ pool. We report that ILC3 were expanded in infected MyD88-/- mice relative to their MyD88+/+ counterparts, suggesting a compensatory response triggered by loss of MyD88. Furthermore, bacterial flagellin and Toxoplasma specific CD4+ T cell populations in the lamina propria expanded in response to infection in both WT and KO mice. Finally, we show that My88-independent IL-12 and T cell mediated IFN-γ production require the presence of the intestinal microbiota. Our results identify MyD88-independent intestinal immune pathways induced by T. gondii including myeloid cell derived IL-12 production, downstream type I immunity and IFN-γ production by ILC1, ILC3, and T lymphocytes. Collectively, our data reveal an underlying network of immune responses that do not involve signaling through MyD88.